2023
DOI: 10.1111/tid.14000
|View full text |Cite
|
Sign up to set email alerts
|

Burden of neutropenia and leukopenia among adult kidney transplant recipients: A systematic literature review of observational studies

Abstract: Background Leukopenia and neutropenia (L/N) may affect treatment decisions, potentially resulting in poor clinical and economic outcomes among kidney transplant recipients (KTRs). The burden of L/N is poorly quantified systematically. This systematic literature review aimed to summarize the incidence of, risk factors for, and clinical and economic outcomes associated with L/N post‐KT. Methods We systematically searched MEDLINE, Embase, and the Cochrane Library (from database inception‐June 14, 2021) and confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Valganciclovir is an inhibitor of CMV DNA polymerase . It commonly causes myelosuppression, especially leukopenia and neutropenia, which can lead to discontinuation/interruption of CMV prophylaxis, dose reduction of immunosuppressants, and/or use of granulocyte colony–stimulating factor(s) (G-CSF) . Valganciclovir requires dose adjustments due to fluctuating kidney function after kidney transplant .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valganciclovir is an inhibitor of CMV DNA polymerase . It commonly causes myelosuppression, especially leukopenia and neutropenia, which can lead to discontinuation/interruption of CMV prophylaxis, dose reduction of immunosuppressants, and/or use of granulocyte colony–stimulating factor(s) (G-CSF) . Valganciclovir requires dose adjustments due to fluctuating kidney function after kidney transplant .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 It commonly causes myelosuppression, especially leukopenia and neutropenia, which can lead to discontinuation/interruption of CMV prophylaxis, dose reduction of immunosuppressants, and/or use of granulocyte colony-stimulating factor(s) (G-CSF). [6][7][8][9] Valganciclovir requires dose adjustments due to fluctuating kidney function after kidney transplant. 6,10 Additionally, valganciclovir (ganciclovir)-resistant CMV has been detected in individuals with prolonged exposure to or subtherapeutic concentrations of valganciclovir (ganciclovir).…”
mentioning
confidence: 99%
“…12,[16][17][18] Even though leukopenia and neutropenia appear to be common post-SOT, previous studies assessing incidence rates and the impact of leukopenia and/or neutropenia on outcomes have been predominantly in kidney and/or liver transplant recipients. 6,[12][13][14]17,[19][20][21] Importantly, the definitions of leukopenia and/or neutropenia in SOT are variable or missing across the medical literature 6,12,21 which limits comparability between studies.…”
Section: Introductionmentioning
confidence: 99%
“…6 Granulocyte-colony stimulating factor (G-CSF) is generally safe in SOT 22,23 but it is associated with significant costs. 6 Some studies have suggested no association between leukopenia and neutropenia and/or rates of graft rejection and/or infection 20,21,24 but others have suggested the contrary. 12 A systematic review assessing the burden of leukopenia/neutropenia in adult kidney transplant recipients by Raval and colleagues showed that CMV D+/R-status, mycophenolic acid, and tacrolimus were the most common risk factors for leukopenia/neutropenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation